2021
DOI: 10.3390/agronomy11112256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deficit Irrigation Scheduling on Water Use, Gas Exchange, Yield, and Fruit Quality of Date Palm

Abstract: Water scarcity is very common in the arid region due to the low yearly rainfall. The cost of water for agricultural usage is extremely high in dry locations. Date palm is a high water-demanding tree throughout the year in arid regions. Therefore, the application of deficit irrigation strategies for date palm cultivation may significantly contribute to conserving irrigation water. The present study aimed to assess the effects of controlled deficit irrigation using two modern micro-irrigation systems on water us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Highest fruit yield and crop water productivity was reported in date palm cvs. Sheshi [42] and Khalas [41] when the trees were irrigated by the subsurface irrigation system at 50% ETc. Another study found that the date palm plant irrigated with a 60% water requirement in the SSDI system showed no significant difference compared to the bubbler system at 100% ETc [79].…”
Section: Yield and Water Productivitymentioning
confidence: 99%
See 3 more Smart Citations
“…Highest fruit yield and crop water productivity was reported in date palm cvs. Sheshi [42] and Khalas [41] when the trees were irrigated by the subsurface irrigation system at 50% ETc. Another study found that the date palm plant irrigated with a 60% water requirement in the SSDI system showed no significant difference compared to the bubbler system at 100% ETc [79].…”
Section: Yield and Water Productivitymentioning
confidence: 99%
“…Subsurface drip irrigation reduces subsurface drainage, manages soil salinity, and enhances tomato yield [40]. In addition, it is not affected by high wind velocity as the water is applied directly to plants' root zones [41,42]. Higher crop yields, saving of water, increased fertilizer use efficiency, reduced energy consumption, tolerance to windy atmospheric conditions, reduced labor cost, minimized pest and disease problems, suitability in sloppy lands, and improved soil tolerance to salinity are just a few advantages of subsurface drip irrigation system over other irrigation methods [10,29,[41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have demonstrated that Cd strongly inhibited the synthesis of chlorophylls and their stable binding to proteins, thereby damaging the photosynthetic apparatus and, in particular, decreasing the concentration of light-harvesting complex II and photosystems I (PSI) and II (PSII) [15,16]. Water is one of the crucial factors limiting crop production in numerous regions worldwide [17,18]. Other studies have indicated that increasing WUE can reduce water stress and improve productivity under stress [19,20].…”
Section: Introductionmentioning
confidence: 99%